Influence of Cognitive Measures on Social Perception in Parkinson's Disease - Dawson, Mary L; Mather, Olivia T. (My University, 2025)
Parkinson’s Disease (PD) is a progressive neurodegenerative disorder that significantly impacts an individual’s mobility, cognition, and overall quality of life. In addition to motor impairments, non-motor symptoms such as cognitive and communicative impairments significantly affect social interactions for individuals with PD. The current study analyzes the effects of PD on perceiving social interactions and how that relates to cognitive skills. A series of dynamic language and cognitive tests are utilized to observe aspects of non-literal language perception in individuals with PD. Neuropsychological testing of PD participants was conducted using the Cognitive Linguistic Quick Test (CLQT) to assess general cognitive skills, in relation to accuracy on the RISC social perception task. The social communication task consisted of video stimuli pulled from the Relational Inference in Social Communication (RISC) database (Rothermich & Pell, 2015). The participants were to identify the speaker’s intent, including whether the speaker was sincere or insincere. The results show that all participants, both participants with PD and healthy controls (HC), had more difficulties in identifying nonliteral statements compared to literal statements. Participants with PD had a harder time recognizing social intent compared to the HC, which may be due to changes in cognitive abilities. For the PD group, analyses showed positive correlations between many cognitive domains and the social communication task. In summary, our study emphasizes the relationship between cognitive skills and social perception impairments in patients with PD and highlights the need to develop diagnostic tools and ways to treat these impairments.
Keywords: Parkinson’s Disease; social communication; nonliteral language; irony; neurodegenerative disease